PVA based gel polymer electrolytes with mixed iodide salts (K+I− and Bu4N+I−) for dye-sensitized solar cell application. (10th November 2015) - Aziz, M.F.; Buraidah, M.H.; Careem, M.A.; Arof, A.K.
Abstract: Polyvinyl alcohol (PVA) based gel polymer electrolytes (GPEs) with mixed iodide salts (KI and Bu4 NI) have been prepared for application in dye sensitized solar cells and characterized using techniques such as X-ray diffraction, Fourier transform infrared spectroscopy, and electrical impedance spectroscopy. The X-ray studies indicated that all GPEs had amorphous character and the FTIR measurements confirmed the weak interaction between the polymer host and salts used. Even though the electrolyte containing only KI as the iodide salt showed the highest conductivity of 12.48 mS cm −1, the electrolyte having 30% KI and 70% Bu4 NI with a moderate conductivity of 5.25 mS cm −1 produced the best efficiency of 5.8% in the DSSC and the best performance is attributed to mixed cation effect arising due to the presence of smaller and larger cations in the electrolyte. Addition of BMII ionic liquid to the best performing GPE enhanced the efficiency to a high value of 6.3% due to the increased number of iodide ions and enhanced mobility of iodide ions.